Avaliação do sopro cardíaco na infância Assessment of heart murmurs in childhood - Maria Elisabeth B.A. Kobinger (Elsevier, 2003)
OBJETIVO: discutir a avaliação clínica e laboratorial do sopro cardíaco, considerando sua alta freqüência no atendimento ambulatorial do pediatra geral. FONTE DE DADOS: revisão baseada na análise crítica da literatura atual e consulta a compêndios de cardiologia pediátrica e pediatria contendo informações básicas sobre o tema. SÍNTESE DOS DADOS: os principais destaques do artigo referem-se à importância da anamnese e exame físico do sistema cardiovascular, essenciais para o pediatra geral diagnosticar o sopro cardíaco inocente, e identificar situações que indiquem a ocorrência de cardiopatias congênitas, ou adquiridas, e a necessidade de encaminhamento ao especialista. CONCLUSÕES: o pediatra geral é geralmente o primeiro médico a detectar um sopro cardíaco e deve estar apto a reconhecer o sopro inocente, assim como a suspeitar precocemente de doenças cardiovasculares. OBJECTIVE: to discuss clinical and laboratorial evaluation of heart murmurs in children, an important problem faced by pediatricians in their practice. SOURCES OF DATA: this review was based on a critical analysis of the current literature, as well as pediatrics and pediatric cardiology textbooks, which were found to be an important source of information on the subject. SUMMARY OS THE FINDINGS: it is important for pediatricians to know how to obtain precise information regarding the patient's medical history and to perform extensive physical examination of a child with heart murmur. The diagnosis of innocent heart murmur is essentially clinical and it can help the pediatrician to identify situations which are associated with cardiovascular diseases. CONCLUSIONS: in our series, short-term video-EEG monitoring established a reliable diagnosis in most patients due to correlation between clinical and EEG data. This procedure was well tolerated by children, including infants and those with psychiatric disorders.